'Can you recommend any good STI apps?' A review of content, accuracy and comprehensiveness of current mobile medical applications for STIs and related genital infections. (24th November 2016) - Gibbs, Jo; Gkatzidou, Voula; Tickle, Laura; Manning, Sarah R; Tilakkumar, Tilna; Hone, Kate; Ashcroft, Richard E; Sonnenberg, Pam; Sadiq, S Tariq; Estcourt, Claudia S
Abstract : Objective: Seeking sexual health information online is common, and provision of mobile medical applications (apps) for STIs is increasing. Young people, inherently at higher risk of STIs, are avid users of technology, and apps could be appealing sources of information. We undertook a comprehensive review of content and accuracy of apps for people seeking information about STIs. Methods: Search of Google Play and iTunes stores using general and specific search terms for apps regarding STIs and genital infections (except HIV), testing, diagnosis and management, 10 September 2014 to 16 September 2014. We assessed eligible apps against (1) 19 modified Health on The Net (HON) Foundation principles; and (2) comprehensiveness and accuracy of information on STIs/genital infections, and their diagnosis and management, compared with corresponding National Health Service STI information webpage content. Results: 144/6642 apps were eligible. 57 were excluded after downloading. 87 were analysed. Only 29% of apps met ≥6 HON criteria. Content was highly variable: 34/87 (39%) covered one or two infections; 40 (46%) covered multiple STIs; 5 (6%) focused on accessing STI testing. 13 (15%) were fully, 46 (53%) mostly and 28 (32%) partially accurate. 25 (29%) contained ≥1 piece of potentially harmful information. Apps available on both iOS and Android were more accurate than single-platform apps. Only one app provided fully accurate and comprehensive information on chlamydia. Conclusions: Marked variation in content, quality and accuracy of available apps combined with the nearly one-third containing potentially harmful information risks undermining potential benefits of an e-Health approach to sexual health and well-being.